PROBLEM BASED LEARNING DENGAN STRATEGI PEMBELAJARAN AKTIF DI SMAN 3 PALANGKARAYA - Endang Sri Suyati (Anterior Jurnal, 2017)
This study aims to: (1) To determine the increased activity of learners during the learning process Economic using Active Learning Strategies Type of Problem Based Learning (Problem Based Learning/PBL) Class X7 SMAN 3 Palangkaraya in academic year 2015/2016. (2) To determine the learning outcome of Economics after using the Active Learning Strategies Type of Problem Based Learning (Problem Based L earning/PBL) Class X7 SMAN 3 Palangkaraya Academic Year 2015/2016.Subjects in this study were all students of class X7 SMAN3 Palangkaraya totaling 37 learners. The method used is using Action Research (PTK). Data collection techniques are observation, documentation, and testing. While the analysis of the data using the percentage of classical completeness. From the results showed that : (1) Activities of learners are more active during the learning process Economic using Active Learning Strategies Type of Problem Based Learning (Problem Based Learning / PBL) Class X7 SMAN 3 Palangkaraya Academic Year 2015/2016, which is indicated by the acquisition observation score above 3, (2) There is an increasing use of learning outcomes Economic Active learning Strategies type of problem Based learning (problem Based learning/PBL) Class X7 SMAN 3 Palangkaraya in academic year 2015/2016. It is seen from the data is the study of students, the first cycle mastery learning outcomes of students that is 64.28% and the second cycle increased to 91.89%. As for the minimum standards prescribed completeness school for Economics lesson is 75.